2023
DOI: 10.1002/adfm.202209407
|View full text |Cite
|
Sign up to set email alerts
|

Wearable, Self‐powered, Drug‐Loaded Electronic Microneedles for Accelerated Tissue Repair of Inflammatory Skin Disorders

Abstract: Electrical stimulation (ES) is widely used in physiological and medical sciences, while its application to treat inflammatory skin diseases (ISDs) remains a challenge owing to their natural pathological cuticle barrier and lack of an effective combination with chemotherapy to achieve specific immunomodulation. Here, a wearable, battery-free, multi-component drugloaded electronic microneedle (mD-eMN) system is developed by integrating remodeled metal microneedles loaded with multi-component chemical drugs and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…6(a), Feng and colleagues introduced a metal microneedle with a sandwich-like structure coated with multicomponent drugs. 66 These MNs penetrate the skin, facilitating drug delivery to inflammatory sites and thereby enhancing drug efficacy. TENGs generate pulsed electrons that promote drug release and penetration into cells for specific immune modulation.…”
Section: Power Supply Methods For Wearable Microneedle Biosensorsmentioning
confidence: 99%
“…6(a), Feng and colleagues introduced a metal microneedle with a sandwich-like structure coated with multicomponent drugs. 66 These MNs penetrate the skin, facilitating drug delivery to inflammatory sites and thereby enhancing drug efficacy. TENGs generate pulsed electrons that promote drug release and penetration into cells for specific immune modulation.…”
Section: Power Supply Methods For Wearable Microneedle Biosensorsmentioning
confidence: 99%
“…It has been reported that continuous as well as pulsed electric fields can influence immune cells such as macrophages by promoting their polarization, cytokine secretion profiles, phagocytic behavior, migration, and differentiation, summarized in Table . In addition to macrophages, electric fields are also known to influence other immune cells such as T and B lymphocytes by modulating their membrane capacities and conductivities which further influence their proliferation, migration, and cytokine profiles. , On the basis of the directionality, two sources of electrical stimulation, namely direct current (DC) and alternating current (AC), have been extensively employed for immunomodulation. , In addition, unidirectional and bidirectional pulsed currents (PCs) which can generate current pulses of around 1 s have been used for immunomodulation owing to lesser electrothermal side effects compared to DC. , …”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
“…In contrast to the reported systems, this self-powered device produced pulsed electrons from TENG directly onto the tissues for increasing the penetration of the drugs which initiated immunomodulation by activating the Ca 2+ signaling pathway. The obtained results showed that a TENG output of 1 V resulted in complete release of the drug within 2 h which inhibited the levels of macrophages and T cells and resulted in a high inhibition efficiency closer to that of normal skin, whereas the only ES group and drug group still had 4.8 and 3.8% cells, respectively, hence validating the efficiency of the combined therapy for alleviating skin inflammation . In addition, ES modalities are also used to deliver next-generation drugs such as short interfering RNAs (siRNAs) which are becoming popular due to the increasing problem of drug resistance with conventional drugs.…”
Section: Electrical Stimulation Combined With Drug Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…When used as a thermoplastic, PA rarely appears in the preparation of W-TENGs, 40,41 because the treated PA can form textile fibers, which increase the specific surface area, are suitable for wearing and enhance the output. Qian et al 42 used a PA66 film as a positive friction layer and assembled it with a commercial PTFE film. When applied to the human neck, a voltage of about 0.6 V is generated; when applied to the wrist, a voltage of about 1 V is generated, which indicates the excellent sensitivity of PA66-PTFE-based W-TENGs favorable for detecting small and low-frequency vibrations of the human body.…”
Section: Friction Layer and Electrode Materials Of The W-tengmentioning
confidence: 99%